2014
DOI: 10.4168/aair.2014.6.1.95
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Codeine Induced Anaphylaxis via Oral Route

Abstract: Codeine is widely prescribed in clinical settings for the relief of pain and non-productive coughs. Common adverse drug reactions to codeine include constipation, euphoria, nausea, and drowsiness. However, there have been few reports of serious adverse reactions after codeine ingestion in adults. Here, we present a case of severe anaphylaxis after oral ingestion of a therapeutic dose of codeine. A 30-year-old Korean woman complained of the sudden onset of dyspnea, urticaria, chest tightness, and dizziness 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A study evaluating the role of SPT in investigating morphine, meperidine, and papaveratum hypersensitivity showed that opiate-sensitive individuals responded similarly as the control study in the SPT, suggesting that this test should not be performed and that placebo-controlled challenge should be considered when possible [76]. Some anaphylactic reports involving opioids have been published, including a recent case of anaphylaxis with codeine, with a positive investigation that included SPT (with negative tests in three healthy controls), histamine-release test, and oral challenge test [77]. However, there is data supporting the safe use of codeine in patients presenting chronic urticaria [78].…”
Section: Opioidsmentioning
confidence: 85%
“…A study evaluating the role of SPT in investigating morphine, meperidine, and papaveratum hypersensitivity showed that opiate-sensitive individuals responded similarly as the control study in the SPT, suggesting that this test should not be performed and that placebo-controlled challenge should be considered when possible [76]. Some anaphylactic reports involving opioids have been published, including a recent case of anaphylaxis with codeine, with a positive investigation that included SPT (with negative tests in three healthy controls), histamine-release test, and oral challenge test [77]. However, there is data supporting the safe use of codeine in patients presenting chronic urticaria [78].…”
Section: Opioidsmentioning
confidence: 85%
“…Allergic reactions to codeine are known, as also shown by newly published case reports, but rarely in a severe form (Fathallah et al., ; Deverriere et al., ; Ariosto, ; Yoo et al., ; Erfan et al., ; Prescribing Information, ).…”
Section: Assessmentmentioning
confidence: 86%
“…It has been found that codeine and morphine are more prone to inducing mast cell degranulation than other opioids [50]. Codeine induces pseudoallergy via a non-immunologic mechanism, which is independent of both IgE and the high-affinity IgE receptor FcεRI [51,52]. The activation of mast cell degranulation by codeine may, therefore, occur through its actions at the opioid receptor [51].…”
Section: Drug-induced Pseudoallergymentioning
confidence: 99%